Armed conflict and the challenge of hunger: Is an end in sight? - de Waal, Alex (Welthungerhilfe, 2015)
War and famine, two fearsome horsemen, have long ridden side by side. Armed conflict disrupts food systems, destroys livelihoods, displaces people, and leaves those who do not flee both terrified and unsure when they will eat their next meal. News stories and scholarly articles on conflict and hunger are usually pessimistic, assuming both are inevitable parts of the human condition. But a review of trends offers cause for optimism: a potential end to famine and conflict-induced starvation by 2030. This chapter examines those trends, identifies vulnerable populations, explores the complex relationship between conflict and hunger, and underscores what must be done to eliminate famine for good.